On the Stewardship Value of Soft Managerial Reports - Şabac, Florin; Tian, Jie (Joyce) (The Accounting Review, 2015)
ABSTRACT We characterize the necessary and sufficient conditions for communication of private, unverifiable managerial information to be valuable for stewardship purposes. First, the hard, verifiable information must be able to confirm to some extent the truthfulness of the manager's soft, unverifiable report. Second, neither the hard, verifiable information nor the soft, unverifiable managerial report should be too informative for providing effort incentives because that makes it harder to motivate truthful reports from the manager. In particular, this conflict can be sufficiently severe that eliciting reports from the manager has no value.